Kajian Etnobotani Arecaceae Pada Masyarakat Kabupaten Lombok Barat - Elite Sulistia; Kurniasih Sukenti; Tri Mulyaningsih (The Ethnobiological Society of Indonesia, 2021)
West Lombok has a wealth of the plantation sector, which is quite superior to several species of Arecaceae such as coconut (Cocos nucifera), areca nut (Areca catechu) and sugar palm (Arenga pinnata). These plants are used for daily needs, for example for food, construction, medicine, social, cultural and economic needs. The use of Arecaceae is widely known and acted by the older generation. This study aims to determine the Arecaceae species that are utilized by the people in West Lombok, their utilization aspects, socio-cultural, economic and conservation aspects. Data collection was carried out by interview, participatory observation, and documentation. Data were analyzed descriptively qualitative and quantitative based on the calculation of Reported Use (RU), Index of Cultural Significance (ICS) and Plant Part Value (PPV). Interviewing 22 informants aged 25-100 years old and dominated by women carried out information gathering. Based on the results of the research, there were 12 species of Arecaceae that were used by the people in West Lombok Regency, they are Cocos nucifera L. (Cocos nucifera var. viridis, Cocos nucifera “Genjah merah” and Cocos nucifera